Who Contributed More on Calculus? Newton or Leibniz? - Jiachen Lu (Studies in Social Science & Humanities, 2023)
Modern calculus is a strong tool in mathematical models and analysis. It is greatly applied in a variety of aspects including astrology, computer science, physics, business, etc. However, its origin has been debated between two great mathematicians from 18th century: Newton and Leibniz. Newton claimed to have invented calculus first, and had used this technique in some of his papers. However, no published records could prove his discovery. Leibniz published the first paper regarding the discovery of calculus “Nova Methodus pro Maximis et Minims” (New Method for the Greatest and the Least). Newton then accused Leibniz of stealing his idea and asserted his credit for inventing calculus. In this essay, to explain the cause of the Newton-Leibniz controversy, the discovery of calculus is evaluated from both Newton’s and Leibniz’s aspects. Their different methods are compared to answer the question: who is the true inventor of calculus?